Transcatheter electrosurgical aortic septostomy optimizes distal landing zone in chronic dissectionCentral MessagePerspective - Alexander P. Nissen, MD; Yazan M. Duwayri, MD; William D. Jordan, MD; Vasilis C. Babaliaros, MD; Robert J. Lederman, MD; Bradley G. Leshnower, MD (JTCVS Techniques)
Objective: Efficacy of thoracic endovascular aortic repair (TEVAR) for chronic type B aortic dissection (CTBAD) is dependent on eliminating retrograde false lumen perfusion and remodeling the aorta. We describe the efficacy of a novel transcatheter electrosurgical technique to fenestrate the dissection flap and create a distal seal zone for TEVAR in CTBAD. Methods: A retrospective review of the Emory Aortic Database from 2016 to 2023 identified 33 patients who underwent TEVAR with intentional endovascular rupture of the dissection flap (Knickerbocker; KNICK) for CTBAD. In 11 patients, we performed transcatheter electrosurgical aortic septostomy (TECSAS) before KNICK. The technical aspects of TECSAS + KNICK are described and results compared with TEVAR + KNICK alone. Results: Dissection chronicity, aortic size, and preoperative demographics were similar between groups. Technical success was 100%, with zero stroke or paraplegia in both groups. Thirty-day mortality for TECSAS versus KNICK was 0% versus 13.6% (P = .199). Median follow-up was shorter after TECSAS versus KNICK, although not statistically significant (14.6 months vs 21.9 months; P = .065). Elimination of retrograde false lumen perfusion (TECSAS 100% vs KNICK 68.2%; P = .035) and complete false lumen thrombosis or obliteration (TECSAS 91.9% vs KNICK 54.6%; P = .037) were more frequent after the TECSAS procedure. Aortic reinterventions were less frequent after TECSAS versus KNICK (0% vs 13.6%, P = .199), although not statistically significant. Conclusions: The addition of TECSAS to intentional endovascular rupture of the dissection flap in CTBAD improves distal seal, eliminating retrograde false lumen perfusion. This technique is a safe and precise method to fenestrate a dissection flap and optimize TEVAR in CTBAD.